PENGARUH PELATIHAN PANCA CARA TEMUAN MAKNA TERHADAP PENURUNAN TINGKAT DEPRESI PADA PASIEN DIABETES MELITUS - Ketut Dian Wahyuni; I Wayan Candra (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2019)
This study aims to prove the effect of panca cara temuan makna training to reduce the degree of depression in diabetes mellitus patients at UPT Kesmas Blahbatuh 1 in 2019. The design of this study was pre-experimental with a one group pre-post test design. The sampling technique that is used was purposive sampling with the sample of 15 people. The results showed that the depression degree of the study subjects before being given treatment was mostly in the moderate depression degree of 11 people (73.3%), after being given treatment most of them were in mild depression degree of 8 people (53.3%), and panca cara temuan makna training influenced the decrease in depression levels in the study subjects with p=0.001 (p 0.050). The conclusions of this study are that there is a significant effect of panca cara temuan makna training to reduce the degree of depression in diabetes mellitus patients at UPT Kesmas Blahbatuh 1 on 2019.